2021
DOI: 10.1063/5.0046917
|View full text |Cite
|
Sign up to set email alerts
|

Electronic processes in organic–inorganic composite P3HT with silicon nanocrystals

Abstract: The generation mechanisms and charge carrier transfer in a composite of polymer poly-3(hexylthiophene) (P3HT) and silicon nanoparticles (nc-Si) films are investigated using conductivity measurements at different temperatures and electric fields and photocurrent spectroscopy. It is shown that the widely used Gaussian disorder model for describing the electrical and optical properties of polymers is also valid for hybrid organic–inorganic materials consisting of polymer matrix with silicon nanoparticles addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…It follows from the results, that an addition of nc-Si considerably decreases conductivity of the material in the direct current mode. Previous studies have shown that the addition of nc-Si to P3HT polymer results in a change in the distribution of the density of localized states, over which the hopping mechanism of charge carriers is implemented [15]. This change takes place due to the change in degree of polymer crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…It follows from the results, that an addition of nc-Si considerably decreases conductivity of the material in the direct current mode. Previous studies have shown that the addition of nc-Si to P3HT polymer results in a change in the distribution of the density of localized states, over which the hopping mechanism of charge carriers is implemented [15]. This change takes place due to the change in degree of polymer crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…Из результатов следует, что добавление nc-Si значительно снижает проводимость материала в режиме постоянного тока. Ранее было показано, что добавление nc-Si в полимер P3HT приводит к изменению плотности распределения локализованных состояний, по которым осуществляется прыжковый механизм переноса носителей заряда [15]. Такое изменение происходит за счет изменения степени кристалличности полимера.…”
Section: экспериментальные результаты и их обсуждениеunclassified